The Effect of Managerial Ownership, Independent Board of Commissioners, Audit Committee, and Firm Size on Financial Distress - Fanliana Tantinaya; Taufeni Taufik; Rheny Afriana Hanif (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to examine the effect of managerial ownership, independent board of commissioners, audit committee, and firm size on financial distress. This research employs a quantitative approach using secondary data obtained from corporate financial statements. The population of this study consists of all property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The sample was selected using a purposive sampling method, resulting in 55 companies that met the predetermined criteria. Logistic regression analysis was used to test the research hypotheses. The results indicate that managerial ownership, audit committee, and firm size have a significant effect on financial distress, while the independent board of commissioners has no significant effect on financial distress.